Exercise activates vagal induction of dopamine and attenuates systemic inflammation - Shimojo, Guilherme (Brain Behav Immun, 2018)
Physical exercise is one of the most important factors improving quality of life, but it is not feasible for patients with morbidity or limited mobility. Most previous studies focused on high-intensity or long-term exercise that causes metabolic stress or physiological adaption, respectively. Here, we studied how moderate-intensity swimming affects systemic inflammation in 6–8 week old C57BL/6J male mice during endotoxemia. One-hour swimming prevented hypokalemia, hypocalcemia, attenuated serum levels of inflammatory cytokines, increased anti-inflammatory cytokines but affected neither IL6 nor glycemia before or after the endotoxic challenge. Exercise attenuated serum TNF levels by inhibiting its production in the spleen through a mechanism mediated by the subdiaphragmatic vagus nerve but independent of the splenic nerve. Exercise increased serum levels of dopamine, and adrenalectomy prevented the potential of exercise to induce dopamine and to attenuate serum TNF levels. Dopaminergic agonist type-1, fenoldopam, inhibited TNF production in splenocytes. Conversely, dopaminergic antagonist type-1, butaclamol, attenuated exercise control of serum TNF levels. These results suggest that vagal induction of dopamine may contribute to the anti-inflammatory potential of physical exercise.